Storage induced conversion of ovalbumin into S-ovalbumin in eggs impacts the properties of pound cake and its batter. (July 2015) - Deleu, Lomme J.; Wilderjans, Edith; Van Haesendonck, Ingrid; Courtin, Christophe M.; Brijs, Kristof; Delcour, Jan A.
Abstract: Storage of shell eggs for 28 days at 6 or 23 °C converts ovalbumin (which represents over 50% of egg white protein) into its more thermostable intermediate and S-ovalbumin forms. Their increased thermostability causes them to expose their sulfhydryl groups only at higher temperatures than does ovalbumin itself. During pound cake baking, the loss in protein extractability under non-reducing conditions (further taken as a measure of protein network formation) occurred later when egg white from stored eggs rather than from fresh eggs was used. The incorporation of the more thermostable forms of ovalbumin ( i.e . intermediate and S-ovalbumin) in the protein network occurred later than did that of ovalbumin. The moment at which ovalbumin denatures determines when the largest decrease in overall protein extractability occurs, which points to ovalbumin having a key role in protein network formation during cake baking. However, at the end of the process, the overall baking induced loss of protein extractability was similar when egg white from either fresh or from stored eggs was used. Rapid Visco Analyser measurements showed that this delay in protein network formation impacts cake batter viscosity. While cakes baked with fresh or stored egg white were of similar volume, cake crumb cohesiveness and springiness of cakes produced with fresh egg white were higher than those of cakes produced with stored egg white. Graphical abstract: Highlights: S-ovalbumin exposes sulfhydryl later during heating than ovalbumin. Ovalbumin plays a key role in the protein network formation in pound cake making. Ovalbumin and S-ovalbumin lead to different protein networks and cake crumb textures.